Adherence to Oral Anticancer Medications: Evolving Interprofessional Roles and Pharmacist Workforce Considerations - Gennaro A. Paolella; Andrew D. Boyd; Scott M. Wirth; Sandra Cuellar; Neeta K. Venepalli; Stephanie Y. Crawford (MDPI AG, 2018)
Interprofessional care is exhibited in outpatient oncology practices where practitioners from a myriad of specialties (e.g., oncology, nursing, pharmacy, health informatics and others) work collectively with patients to enhance therapeutic outcomes and minimize adverse effects. Historically, most ambulatory-based anticancer medication therapies have been administrated in infusion clinics or physician offices. Oral anticancer medications (OAMs) have become increasingly prevalent and preferred by patients for use in residential or other non-clinic settings. Self-administration of OAMs represents a significant shift in the management of cancer care and role responsibilities for patients and clinicians. While patients have a greater sense of empowerment and convenience when taking OAMs, adherence is a greater challenge than with intravenous therapies. This paper proposes use of a qualitative systems evaluation, based on theoretical frameworks for interdisciplinary team collaboration and systems science, to examine the social interactionism involved with the use of intravenous anticancer treatments and OAMs (as treatment technologies) by describing patient, organizational, and social systems considerations in communication, care, control, and context (i.e., Kaplan's 4Cs). This conceptualization can help the healthcare system prepare for substantial workforce changes in cancer management, including increased utilization of oncology pharmacists.